Are Exposures to Multiple Frequencies the Key to Future Radiofrequency Research? - Sienkiewicz, Zenon; Calderón, Carolina; Broom, Kerry A.; Addison, Darren; Gavard, Amélie; Lundberg, Louise; Maslanyj, Myron (Frontiers in Public Health, 2017)
There is an extensive literature investigating possible effects of exposure to radiofrequency (RF) electromagnetic fields associated with mobile phone technologies. This has not identified any public health risks with any degree of certainty. Some epidemiological studies have observed associations between heavy users of mobile phones and some types of cancer, but animal studies do not support this association, although a few studies have reported increased tumor yields. However, there is a crucial difference between epidemiology studies and laboratory work in terms of signals investigated: most people are exposed to a complex mixture of frequencies and signals at varying intensities, whereas the majority of animal studies have been performed using a single frequency or intensity. Whether this might explain the differences in outcome will be discussed, and whether there is a need for additional laboratory investigations that reproduce more accurately realistic exposure conditions will be considered.